Libertad y justicia en las sociedades modernas - Salinas de Gortari, Carlos (México, D.F. : M.A. Porrúa Grupo Editorial, 1994)
"Contains some 50 essays dealing with ideological change, social welfare, individualism, liberty and justice, citizenship, governability, and political economy, presented at a conference funded by the Mexican Government. Authors include both leading Mexican and internationally distinguished scholars and intellectuals"--Handbook of Latin American Studies, v. 57.
Descripción basada en recurso en línea; Título de la página del título en PDF (e-libro, visto June 08, 2015).
Recurso electrónico. Santa Fe, Arg.: e-libro, 2015. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a e-libro.
Keywords: Libertad; Justicia; Capitalismo; Democracia; Liberty -- Congresses; Justice -- Congresses; Capitalism -- Congresses; Democracy -- Congresses; Nationalism -- Congresses; Libros electrónicos.